Dark fermentative hydrogen production from hydrolyzed sugar beet pulp improved by iron addition. (October 2020) - Cieciura-Włoch, Weronika; Borowski, Sebastian; Domański, Jarosław
Highlights: Hydrolyzed sugar beet pulp produced both hydrogen and methane, despite low pH. Addition of 1 gFe2 O3 /dm 3 gave the highest hydrogen yield of 58.9 dm 3 /kgVS. Family XIII and Ruminococcaceae were dominant H2 -producing bacteria. Lactic acid producing bacteria and methanogens hampered hydrogen production. Abstract: This study evaluated the impact of three different iron compounds (Fe2 O3, FeSO4, FeCl3 ) on hydrogen production via mesophilic dark fermentation (DF) of hydrolyzed sugar beet pulp (SBP). In batch tests, the maximum hydrogen yield of over 200 dm 3 H2 /kgVS was achieved with the addition of 0.1 gFe2 O3 /dm 3, which was twice greater than the control. In semi-continuous experiments, the highest hydrogen production of 52.11 dm 3 H2 /kgVS combined with 19.4 dm 3 CH4 /kgVS methane yield was obtained at a dose of 1 gFe2 O3 /dm 3 . Acetic, lactic and caproic acids were the main metabolic products of DF. Microbiological studies showed some balance between hydrogen producing microorganisms from the order Clostridiales and lactic acid producers (LAB) affiliated with the orders Lactobacillales and Coriobacteriales . Moreover, the presence of methanogens affiliated to the genera Methanobrevibacter and Methanosphaera was also documented. An interesting finding was the appearance of rare bacteria from the genus Caproiciproducens, which was responsible for increased caproic acid production.